2016
DOI: 10.5735/086.053.0601
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Food Resources, Reproductive Rate and Hunting Pressure on the Baltic Grey Seal Population in the Finnish Sea Area

Abstract: Grey sealRinged seal Harbour sealThe indicator includes all species of seals that occur in the Baltic Sea and is applicable in the whole HELCOM area. The status evaluation is presented separately for the three seal species. The grey seal in the Baltic proper is evaluated as a single unit, whereas the Kattegat grey seals are evaluated separately. The status of ringed seals is evaluated for two management units and harbour seals for four units. The evaluation of abundance of seals is based on data from 2014.Grey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…The increasing herring weight in recent years thus likely caused the increase in the blubber thickness of adult females in the Bothnian Bay. Furthermore, an earlier study (Kauhala et al 2016) showed that the birth rate (% mature females giving birth each year) of gray seals increased during recent years with increasing herring weight. Blubber thickness of hunted adult females also partly explained the variation in the birth rate of gray seal females (birth rate from Kauhala et al 2016: Table 2; r 2 = 0.53, F = 8.9, df = 1, 6, p = 0.024) in recent years.…”
Section: Importance Of Herring Quality On Baltic Gray Sealsmentioning
confidence: 96%
See 1 more Smart Citation
“…The increasing herring weight in recent years thus likely caused the increase in the blubber thickness of adult females in the Bothnian Bay. Furthermore, an earlier study (Kauhala et al 2016) showed that the birth rate (% mature females giving birth each year) of gray seals increased during recent years with increasing herring weight. Blubber thickness of hunted adult females also partly explained the variation in the birth rate of gray seal females (birth rate from Kauhala et al 2016: Table 2; r 2 = 0.53, F = 8.9, df = 1, 6, p = 0.024) in recent years.…”
Section: Importance Of Herring Quality On Baltic Gray Sealsmentioning
confidence: 96%
“…Furthermore, an earlier study (Kauhala et al 2016) showed that the birth rate (% mature females giving birth each year) of gray seals increased during recent years with increasing herring weight. Blubber thickness of hunted adult females also partly explained the variation in the birth rate of gray seal females (birth rate from Kauhala et al 2016: Table 2; r 2 = 0.53, F = 8.9, df = 1, 6, p = 0.024) in recent years. Nutritional status (or body mass) of female seals may thus have an impact on reproduction (age at sexual maturity, ovulation rate, implantation of embryos, and maintenance of pregnancy) of seal females (e.g., Boyd 1984;Boyd et al 1999;Harwood et al 2000;Bowen et al 2006Bowen et al , 2015.…”
Section: Importance Of Herring Quality On Baltic Gray Sealsmentioning
confidence: 96%
“…Ovaries were removed, and cross sections made by knife were examined by naked eye for the presence of corpus albicans (CA). Birth rate was determined as the proportion of females with CA from the spring sample (April-June; see also Kauhala et al 2014Kauhala et al , 2016. Corpus luteum atrophies to CA after parturition and remains until mid-summer when a new embryo implants into the uterus but may disappear after mid-summer if the female is not pregnant (Hewer 1964 .…”
Section: Study Area and Seal Samplesmentioning
confidence: 99%
“…It is a generalist predator preying on several fish species (Lundström et al 2007(Lundström et al , 2010Kauhala et al 2011;Scharff-Olsen et al 2018;Tverin et al 2019). In the Finnish sea area, Baltic herring (Clupea harengus membras) is the most common prey fish for grey seals, and herring quality is related with body condition and reproductive rate of seals (Kauhala et al 2016(Kauhala et al , 2017(Kauhala et al , 2019. Another common prey fish for grey seals is the sprat (Sprattus sprattus), especially in the southern part of the Finnish sea area (Kauhala et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation